Bauran Pemasaran (Marketing Mix) Tanaman Hias pada CV. Kumala Dewata di Kecamatan Denpasar Barat, Kota Denpasar - ROMAN UMBU HAUMARA; I KETUT SUAMBA; I PUTU DHARMA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
The Marketing Mix of Ornamental Plants at CV. Kumala Dewata in theSub-District of Western Denpasar, City of DenpasarThe marketing mix is a combination of four variables that are the core of thecompany's marketing system consisting of : product, price, distribution, andpromotion. The aim of the research is to determine the marketing mix ofornamental plants on the CV. Kumala Dewata and the constraints found in themarketing activities. The research location was selected intentionally (purposively).The data types include primary and secondary data. The data were collected byobservation, in-depth interview, and documentation study. Data were analyzeddescriptively and qualitatively. Based on the research results, it was found that themarketing mix carried out by the company on the products, namely : market avariety of ornamental plants in the landscape project to suit the consumers’demands, guarantee the plants and is responsible for information and theconsumers’ complaints. Pricing used the cost approach and frequent discounts.Pricing for landscape projects and maintenance uses the cost approach. Paymentsby cash and credit. Distribution of products is conducted directly. Servicedistribution is done by approaching the consumers. Marketing areas include hotels,villas, and restaurants scattered in the Province of Bali. Distribution of facilitiesuses a pick-up car. Promotions use personal sales through ACE organization inBali. The obstacles faced, namely the damage of ornamental plants, the increase infuel prices, a shortage of labor, delayed working process, the limited use ofmethods of promotion, the noisy atmosphere made by the outsourcing staffs and theequipments that led to complaints from the hotel guests, capital limitation in theprovision of agricultural lands, and the expenditure was more spent for equipmentthat did not achieve the economic life.